Regional hyperperfusion in older adults with objectively-defined subtle cognitive decline. Issue 5 (May 2021) - Thomas, Kelsey R; Osuna, Jessica R; Weigand, Alexandra J; Edmonds, Emily C; Clark, Alexandra L; Holmqvist, Sophia; Cota, Isabel H; Wierenga, Christina E; Bondi, Mark W; Bangen, Katherine J
Although cerebral blood flow (CBF) alterations are associated with Alzheimer's disease (AD), CBF patterns across prodromal stages of AD remain unclear. Therefore, we investigated patterns of regional CBF in 162 Alzheimer's Disease Neuroimaging Initiative participants characterized as cognitively unimpaired (CU; n  = 80), objectively-defined subtle cognitive decline (Obj-SCD; n  = 31), or mild cognitive impairment (MCI; n  = 51). Arterial spin labeling MRI quantified regional CBF in a priori regions of interest: hippocampus, inferior temporal gyrus, inferior parietal lobe, medial orbitofrontal cortex, and rostral middle frontal gyrus. Obj-SCD participants had increased hippocampal and inferior parietal CBF relative to CU and MCI participants and increased inferior temporal CBF relative to MCI participants. CU and MCI groups did not differ in hippocampal or inferior parietal CBF, but CU participants had increased inferior temporal CBF relative to MCI participants. There were no CBF group differences in the two frontal regions. Thus, we found an inverted-U pattern of CBF signal across prodromal AD stages in regions susceptible to early AD pathology. Hippocampal and inferior parietal hyperperfusion in Obj-SCD may reflect early neurovascular dysregulation, whereby higher CBF is needed to maintain cognitive functioning relative to MCI participants, yet is also reflective of early cognitive inefficiencies that distinguish Obj-SCD from CU participants.